Performance of two transferred modules in the Lagunera Region: water relations - Levine, G.; Galvan, A.C.; García, D.; Garcés-Restrepo, C.; Johnson, S.H. (International Water Management Institute, 1998)
Evaluates the degree of success of water users in managing water allocations and deliveries in two irrigation district modules in the Lagunera Region of Mexico. Policies and practices are evaluated from the standpoints of the nature of planning rules, consistency, equity, and efficiency in implementation of the plans.